Women Workers in India : Why So Few Among So Many? - Das, Sonali (IMF Working Papers; Working Paper, 2015)
This paper examines the determinants of female labor force participation in India, against the backdrop of India having one of the lowest participation rates for women among peer countries. Using extensive Indian household survey data, we model the labor force participation choices of women, conditional on demographic characteristics and education, as well as looking at the influence of state-level labor market flexibility and other state policies. Our main finding is that a number of policy initiatives can help boost female economic participation in the states of India, including increased labor market flexibility, investment in infrastructure, and enhanced social spending.